PENGARUH KEPERCAYAAN DAN DAYA TARIK BEAUTY VLOGGER TERHADAP KEPUTUSAN PEMBELIAN BEDAK TABUR PIXY - Dinda Ayu Febriana; Sugeng Purwanto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Marketing is a critical component of any business that deals directly with customers. A corporation's marketing management improves optimal purchasing decisions to meet company goals. To maximize buying decisions, consider the relevance of trust and the attractiveness of beauty vloggers while reviewing a product. The goal of this study was to see how the confidence variable (X1) and attractiveness variable (X2) affected purchasing decisions (Y) for pixy powder products in Gresik Regency. Using the probability sampling technique as a sample determination based on standards. This study uses the Partial Least Squares SEM method as a tool for analysis. The variables trust (X1) and attractiveness (X2) were found to have a considerable positive effect on the purchasing decision variable (Y). According to R2, the trust and attractiveness of beauty vloggers influence 50% of purchasing decisions.